2001
DOI: 10.1099/00221287-147-11-2885
|View full text |Cite
|
Sign up to set email alerts
|

Role of the polymorphic region 1 of the Bordetella pertussis protein pertactin in immunity

Abstract: In several countries pertussis is re-emerging, despite a high vaccination coverage. It is suggested that antigenic divergence between Bordetella pertussis vaccine strains and circulating strains, in particular with respect to pertactin, has contributed to pertussis re-emergence. Polymorphism in pertactin is essentially limited to region 1, which is composed of repeats and is located adjacent to an Arg-Gly-Asp motif implicated in adherence. Evidence is provided for the immunological relevance of polymorphism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
0
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 39 publications
7
95
0
11
Order By: Relevance
“…This T1 loop comprises a proline-rich repeat, GGXXP 5 , designated "region 1," which is polymorphic in different clinical isolates and vaccine strains (336). Antibodies to this region have been found in patients with pertussis and are associated (246). The passenger domain of pertactin is the largest ␤-helix described to date, having 16 rungs or coils.…”
Section: Pertactinmentioning
confidence: 99%
“…This T1 loop comprises a proline-rich repeat, GGXXP 5 , designated "region 1," which is polymorphic in different clinical isolates and vaccine strains (336). Antibodies to this region have been found in patients with pertussis and are associated (246). The passenger domain of pertactin is the largest ␤-helix described to date, having 16 rungs or coils.…”
Section: Pertactinmentioning
confidence: 99%
“…An important question is whether the observed mismatches affect the efficacy of pertussis vaccines. Using a mouse model, we have found that variation in Prn affects the efficacy of a WCV (21). One may argue that, since ACVs induce higher titers against Ptx and Prn compared to WCV, they may be less affected by the mismatch.…”
mentioning
confidence: 99%
“…However, their efficacy against subclinical infection is doubtful, as the majority of vaccinated populations test positive for subsequent infection (10,17), suggesting that the bacterium successfully infects immune and/or vaccinated individuals. Using animal models, we and others have previously shown that although B cells are necessary for B. pertussis clearance from the respiratory tract (18)(19)(20), adoptively transferred serum antibodies have little or no effect on bacterial numbers for the first 7 days after inoculation (18)(19)(20)(21) but begin to control and clear the bacteria thereafter. The ability to resist rapid antibody-mediated clearance may increase the duration and intensity of infection, both of which facilitate the transmission of the bacteria and would therefore be critical to the endemism of B. pertussis in vaccinated populations.…”
Section: Introductionmentioning
confidence: 99%